THE IMPACT OF TECHNOLOGY ON MODERN SOCIETY - Юлдуз Бахтияровна, Умарова; Madina, Khalmuratova (Recent scientific discoveries and methodological research, 2024)
This article examines the positive and negative impacts of technology on modern society. It highlights its importance in improving communication, access to information, and efficiency in daily life. The paper also addresses challenges such as privacy issues, the digital divide, and overreliance on technology.